2011
DOI: 10.1186/1471-244x-11-142
|View full text |Cite
|
Sign up to set email alerts
|

The relaxation exercise and social support trial-resst: study protocol for a randomized community based trial

Abstract: BackgroundStudies suggests a possible link between vaginal discharge and common mental distress, as well as highlight the implications of the subjective burden of disease and its link with mental health.Methods/DesignThis is a community-based intervention trial that aims to evaluate the impact of a psycho-social intervention on medically unexplained vaginal discharge (MUVD) in a group of married, low-income Lebanese women, aged 18-49, and suffering from low to moderate levels of anxiety and/or depression. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…The total score, showing emotional stress, is the average of all 25 questions while the depression score is the average of depression items and ranges between 1 and 4. Previous studies indicated good evidence that the Arabic version of the HSCL-25 is reliable and valid (Kobeissi et al 2011). In the present study, the baseline administration of the checklist yielded a Cronbach's α value of 0.87, indicating good reliability for items.…”
Section: Methodsmentioning
confidence: 96%
“…The total score, showing emotional stress, is the average of all 25 questions while the depression score is the average of depression items and ranges between 1 and 4. Previous studies indicated good evidence that the Arabic version of the HSCL-25 is reliable and valid (Kobeissi et al 2011). In the present study, the baseline administration of the checklist yielded a Cronbach's α value of 0.87, indicating good reliability for items.…”
Section: Methodsmentioning
confidence: 96%
“…Each item is rated on a 4-point Likert scale that ranges from 1 to 4 (1 = Not at all, 2 = A little, 3 = Quite a bit, 4 = Extremely). Previous studies with an Arabic version indicated that HSCL-25 is statistically reliable (Acarturk et al, 2016;Kleijn et al, 2001;Kobeissi et al, 2011). The cut-off score of 1.75 and above indicates clinically relevant level of anxiety and depression symptoms (Aragona et al, 2013;Hasanovi c & Herenda, 2008;Mollica et al, 1996).…”
Section: Hscl-25mentioning
confidence: 98%
“…The above study was conducted to reassess the reliability of the tool which has been widely used to measure somatic symptoms. [ 3 4 5 6 7 8 9 10 ] Since, there are going to be significant changes in the classification of somatoform disorders and focus is on the medically unexplained symptoms, it was pertinent to establish whether the tool maintained its test retest reliability and also inter-rater reliability.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Scale for assessment of somatic symptoms (SASS) has been in use since the mid-1980s until date. [3][4][5][6][7][8][9][10][11] It has been used in assessing somatic symptoms and somatization in different groups of general medical,…”
Section: On Somatic Symptoms Measurement: the Scale For Assessment Of Somatic Symptoms Revisitedmentioning
confidence: 99%
See 1 more Smart Citation